What do athlete's really think? Athlete perceptions and attitudes towards athlete monitoring in professional soccer - Woolmer, E.; Morris, R.; Noon, M.; Tallis, J.; Clarke, N. D.; Eyre, E. (International Journal of Sports Science & Coaching, 2025)
Over the past 20 years, monitoring in soccer has become increasingly popular for managing training loads, preventing injuries, and optimizing performance. However, implementing sophisticated systems demands substantial investment in equipment, staff training, and athlete time. The present study aimed to evaluate player's perceptions around a comprehensive athlete monitoring programme used within a professional English men's soccer team. A mixed-methods sequential explanatory design was employed across two phases. In Phase one, 20 professional male soccer players completed a `Modified Athlete Attitudes and Beliefs Questionnaire`. The results from Phase 1 informed Phase 2, where a subset of participants (n = 10) engaged in semi-structured interviews to gain deeper insights into their attitudes and perceptions of athlete monitoring. Analysis revealed that GPS monitoring was the most favoured tool, while power monitoring (countermovement jump; CMJ) was the least preferred. Thematic analysis of interview data identified an overall theme of importance, broken down into four key themes: education, feedback, adjustment period, and specific monitoring tools. To enhance athlete engagement, practitioners should emphasize the relevance of each monitoring strategy to the athletes` performance. Streamlining monitoring strategies and providing more comprehensive feedback can foster greater athlete buy-in and adherence to monitoring programmes.